Glacier and ocean variability in Ata Sund, west Greenland, since 1400 CE - Ekblom Johansson, Fanny Maria; Wangner, David J; Bakke, Jostein; Snowman Andresen, Camilla; Støren, Eivind Wilhelm Nagel; Schmidt, Sabine; Vieli, Andreas (The Holocene, 2020)
To improve knowledge of marine-terminating glaciers in western Greenland, marine sediment cores from the Ata Sund fjord system, hosting two outlet glaciers, Eqip Sermia and Kangilerngata Sermia, were investigated. The main objective was to reconstruct glacial activity and paleoceanographic conditions during the past 600 years. Ice-rafted debris (IRD) was quantified by wet-sieving sediment samples and by using a computed tomography scan. Variability in relative bottom water temperatures in the fjord was reconstructed using foraminiferal analysis. On the basis of this, three periods of distinct glacial regimes were identified: Period 1 (1380–1810 CE), which covers the culmination of the Little Ice Age (LIA) and is interpreted as having advanced glaciers with high IRD content. Period 2 (1810–1920 CE), the end of the LIA, which was characterised by a lowering of the glaciers’ calving flux in response to climate cooling. During Period 3 (1920–2014 CE), both glaciers retreated substantially to their present-day extent. The bottom water temperature started to decrease just before Period 2 and remained relatively low until just before the end of Period 3. This is interpreted as a local response to increased glacial meltwater input. Our study was compared with a study in Disko Bay, nearby Jakobshavn Glacier and the result shows that both of these Greenlandic marine-terminating glaciers are responding to large-scale climate change. However, the specific imprint on the glaciers and the different fjord waters in front of them result in contrasting glacial responses and sediment archives in their respective fjords. publishedVersion